Work and life integration: trajectories of basic health care workers and the construction of their professional identity (Cadernos de Psicologia Social do Trabalho, 2012)
This paper results from an outline of a scientific investigation with a qualitative design focusing on the daily work of basic health care professionals in the city of Florianopolis. It started from the assumption that the professional trajectories experienced by these workers, before and during their tenure as municipal employees, consist in constituent and essential elements for the construction of their identity as health care professionals. Ten professionals from different functional categories who work at different health centers were interviewed. The results, analyzed having discourse analysis as a basis, on their professional trajectories and the meanings they attribute to work, showed a close relationship between their work and life. This close binding comes from the deep identification with their work activities, as well as from their professional qualification initiatives connected to their life experiences. It also results from different meanings attributed to work, comprising both an appreciation of the individual/personal dimension determining their professional trajectories and values from the human/generic dimension, such as conceptions on the public service where they work, recognizing themselves as participants of a working team in which both dimensions are interwoven.